2010
DOI: 10.3382/ps.2009-00233
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of limit feeding corn and distillers dried grains with solubles in non-feed-withdrawal molt programs for laying hens

Abstract: An experiment was conducted using 504 Hy-Line W-36 Single Comb White Leghorn hens (69 wk of age) randomly assigned to 1 of 7 treatments. These treatments consisted of a 47% corn:47% soy hulls diet (C:SH) fed ad libitum; a 94% corn diet fed at a rate of 36.3, 45.4, or 54.5 g/hen per day (CORN 36, CORN 45, and CORN 54, respectively); and a 94% corn distillers dried grains with solubles (DDGS) diet fed at the same rates as the previous corn diets (DDGS 36, DDGS 45, and DDGS 54, respectively) during the molt perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
13
1
Order By: Relevance
“…To reduce stress and induce molting, the hens in this study were subjected only to 7 d of low density feed, instead of feed and water withdrawal. Feeding crushed corn only to induce molting has not been reported to alter post-molting performance [8]. It appears that the method used in our study did not severely affect the physiological requirements of the hens.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…To reduce stress and induce molting, the hens in this study were subjected only to 7 d of low density feed, instead of feed and water withdrawal. Feeding crushed corn only to induce molting has not been reported to alter post-molting performance [8]. It appears that the method used in our study did not severely affect the physiological requirements of the hens.…”
Section: Resultsmentioning
confidence: 51%
“…Diet 1 (control) was not supplemented with Se or Zn [8]; Diet 2 was supplemented with Se only (0.3 ppm/kg of feed); Diet 3 was supplemented with Zn only (20 ppm/kg of feed); and Diet 4 was supplemented with Se (0.3 ppm/kg) and Zn (20 ppm/kg) of feed. Hens were provided water with the diets ad libitum for 5 wks.…”
Section: Experimental Design Diets and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar responses were observed in a study conducted by Mejia et al (2011) where varying levels of DDGS with corn, wheat middlings, and soybean hulls were limit fed. In contrast, Mejia et al (2010) had earlier reported that limit feeding high DDGS diets did result in total cessation or zero egg production in a nonfeed-withdrawal molt program in an earlier study. It is hypothesized that the inconsistent results with DDGS in molt diets among studies may be due to the source and quality of the DDGS.…”
Section: Introductionmentioning
confidence: 67%
“…Generally, such substances are mainly extracted from the crops and so-called co-products (e.g., soybean meal, rapeseed meal, and cotton seed meal; see [91]) could be available for animal nutrition. Except for the extracted nutrient(s), co-products do not vary strongly from their isogenic counterparts in the composition of main nutrients [156,157], but analyses are necessary for the composition of such co-products.…”
Section: Pro Contramentioning
confidence: 99%